2019
DOI: 10.1186/s12302-019-0185-1
|View full text |Cite
|
Sign up to set email alerts
|

Testing effects of pesticides on macroinvertebrate communities in outdoor stream mesocosms using carbaryl as example test item

Abstract: Background: In mesocosms, the fate and effects of chemicals can be investigated under more realistic conditions than in laboratory-scale experiments and most mesocosm studies for higher-tier risk assessment are conducted in lentic test systems. However, particularly for the assessment of EPT taxa (Ephemeroptera, Plecoptera, Trichoptera) and gammarids (Amphipoda), which are considered to be ecologically vulnerable macroinvertebrates, lotic systems seem to be more appropriate. Within this pilot study, eight newl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…The liver in fish serves as the primary detoxification organ, tasked with neutralizing and clearing exogenous compounds [ 27 ]. Under the stress of exposure to the pesticide carbaryl, antioxidant enzymes such as SOD, GSH-Px, and CAT play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…The liver in fish serves as the primary detoxification organ, tasked with neutralizing and clearing exogenous compounds [ 27 ]. Under the stress of exposure to the pesticide carbaryl, antioxidant enzymes such as SOD, GSH-Px, and CAT play a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, in the present study macroinvertebrate assemblages at UNR showed a higher abundance and richness of taxa sensitive to organic contamination such as Trichoptera (Glossosomatidae and Hydropsychidae) and Ephemeroptera (Leptophlebiidae, Baetidae and Caenidae) than at DNR. These groups are widely accepted as bioindicators of good water quality (Brasil et al 2014;Kubendran et al 2017;Thamsenanupap et al 2021) and are highly sensitive to agricultural pollution, including nutrients and pesticides (Schulz et al 2002;Beketov 2004;Thiere and Schulz 2004;Beuter et al 2019;Vilenica et al 2020;Rojas-Peña et al 2021).…”
Section: D��������� ��� C����������mentioning
confidence: 99%
“…Exposure to chemical pollutants including metals, petrochemicals, and pesticides have been shown to cause population level impacts on riverine invertebrate communities (Clements, 1994;Scoggins et al, 2007;Beketov et al, 2009;Byrne et al, 2013). Specifically with regards to pesticides, impacts on invertebrate communities, these have been noted worldwide, including from South America, Africa, USA and Europe (Schriever et al, 2007;Beketov et al, 2013;Chiu et al, 2016;Hunt et al, 2017;Macchi et al, 2018;Beuter et al, 2019;Ganatra et al, 2021). Pesticides shown to impact on riverine invertebrate communities around the world largely belong to the pyrethroid and organophosphate classes (Schriever et al, 2007;Beketov et al, 2013;Chiu et al, 2016;Hunt et al, 2017;Macchi et al, 2018;Ganatra et al, 2021).…”
Section: Introductionmentioning
confidence: 99%